2012
DOI: 10.1093/carcin/bgs176
|View full text |Cite
|
Sign up to set email alerts
|

The essential role of PIM kinases in sarcoma growth and bone invasion

Abstract: PIM kinases are a family of serine/threonine kinases composed of three different isoforms (PIM1, PIM 2 and PIM 3) that are highly homologous. Their expression is mediated by the JAK/STAT signalling pathway, providing survival and cell cycle transition signals. PIM kinases are heavily targeted for anticancer drug discovery. However, very little is known about the relative contribution of the different isoforms to the tumourigenesis process in vivo, and how their individual inhibition might affect tumour growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 60 publications
5
34
0
Order By: Relevance
“…The inactivation of one PTEN allele also works in conjunction with hormone treatments to increase the severity of prostate, bladder, and ureteral urothelial hyperplasia (111113). These findings are consistent with a study showing that the prostate epithelial cells of castrated PTEN(-/-) mice will undergo massive apoptosis, unless they are treated with an mTOR inhibitor (114).…”
Section: Pi3k Pathway In Human Tumorsmentioning
confidence: 99%
“…The inactivation of one PTEN allele also works in conjunction with hormone treatments to increase the severity of prostate, bladder, and ureteral urothelial hyperplasia (111113). These findings are consistent with a study showing that the prostate epithelial cells of castrated PTEN(-/-) mice will undergo massive apoptosis, unless they are treated with an mTOR inhibitor (114).…”
Section: Pi3k Pathway In Human Tumorsmentioning
confidence: 99%
“…Using the TKO mice generated by Mikkers et al, we explored whether the inhibition of specific isoforms is required to prevent the sarcomas induced by treatment with the carcinogen 3-methylcholanthrene (44). We showed that the absence of Pim2 and Pim3 greatly reduced sarcoma growth and that the extent of this reduction was similar to that observed in the absence of all three isoforms.…”
Section: Pim Knock-out Micementioning
confidence: 99%
“…By decreasing the abundance of HSP90AA1 in cancer cells, 2-24a/Cu could decrease the stability of HSP90AA1 client proteins, many of which are critical in tumor initiation and metastasis. Consistent with this hypothesis, PIM1 (a client protein of HSP90AA1 that affects sarcoma growth and bone invasion [21, 22, 30, 31]) is rapidly decreased in the 2-24a/Cu-treated cells. Similarly, AKT1, which affects cell-cycle arrest and apoptosis [22], is concomitantly decreased in the 2-24a/Cu-treated cells.…”
Section: Discussionmentioning
confidence: 70%
“…PIM1 is a client protein of HSP90AA1 in oncogenesis [1], and plays important roles in sarcoma growth and bone invasion [21]. PIM1 protein was significantly decreased in the 2-24a/Cu-treated U2os and HeLa cells (Figure 4A and B).…”
Section: Resultsmentioning
confidence: 99%